Knowledge Production for All - Maldonado-Maldonado, Alma; Lee, Jenny J. (International Higher Education, 2018)
In the current knowledge society, all students and scholars, particularly in nonresearch universities, should learn how to be active contributors, rather than mere consumers, of knowledge. Global knowledge production would be severely weakened and higher education systems would be further stratified if this role was limited to research universities.